My grandma is wonderful - Butterworth, Nick. (Cambridge, Mass. : Candlewick Press, 2003)
Relates the wonderful things Grandma does, from buying the biggest ice cream cones to always having what you need in her pocketbook.
First published: London : Walker, 1991.
1.5.
1.5
K-3
Keywords: Grandmothers -- Fiction; Grandparent and child -- Fiction; Grandmothers -- Fiction; Grandparent-grandchild relationship -- Fiction